Wanprestasi Kewajiban Perusahaan yang Pailit: Studi Kasus PT Merpati Nusantara Airlines - Manalu, Bryan Septian; Hidayanto, Nur Jantra; Rahmadia, Mohamad Haikal; Tanjung, Salsas Bila Juniyanti; S, Surahmad (Media Hukum Indonesia (MHI), 2025)
Bankruptcy is a legal mechanism used to resolve debts when a debtor is unable to fulfill their obligations. This study examines the bankruptcy case of PT Merpati Nusantara Airlines, a State-Owned Enterprise (SOE) operating in the aviation sector. The purpose of this study is to analyze the form of legal protection provided to creditors during bankruptcy proceedings, as well as the legal resolution process applied to PT Merpati Nusantara Airlines. A descriptive qualitative method was employed through a literature review of relevant regulations and court decisions. The results indicate that legal protection for creditors in bankruptcy is regulated through the classification of creditors into three categories: concurrent, secured (separatis), and preferred (preferen) creditors—each with different rights and priorities. Meanwhile, the bankruptcy process of PT Merpati Nusantara Airlines involved several complex stages, beginning with the bankruptcy petition filed by PT Perusahaan Pengelola Aset (PPA), the declaration of bankruptcy by the Commercial Court, and the management of assets by the appointed curator.